Back Cover: pH‐Cleavable Nucleoside Lipids: A New Paradigm for Controlling the Stability of Lipid‐Based Delivery Systems (ChemMedChem 11/2015). Issue 11 (November 2015) - Oumzil, Khalid; Benizri, Sébastien; Tonelli, Giovanni; Staedel, Cathy; Appavoo, Ananda; Chaffanet, Max; Navailles, Laurence; Barthélémy, Philippe
Abstract : The back cover picture shows Orthoester Nucleoside Lipids (ONLs) allowing the formation of pH‐cleavable liposomes. These hybrid nucleolipids can be hydrolyzed at a biologically relevant pH to provide nontoxic nucleoside derivatives and hexadecanol. When ONLs are mixed with natural phosphocholine lipids, the liposomes evolve towards the formation of lamellar systems. Stable Nucleic Acid Lipid Particles (SNALPs) formulated with siRNAs and ONLs were able to release their nucleic acid payload in response to an intracellular acidic environment. More details can be found in the Communication by Philippe Barthélémy et al. onpage 1797 in Issue 11, 2015 (DOI:10.1002/cmdc.201500381 ).